Silagem de grãos úmidos de milho para suínos: digestibilidade e balanços metabólicos - Silva, Adalberto dos Anjos da (2005)
The objective of this work was to evaluate the digestibility and metabolic balances of high moisture corn silage in growing pigs. This rapport present a literature review, experimental procedures, general discussion, conclusions and perspectives about high moisture corn silage. Two trials was realized. Twelve littermates barrows, weighting 47 kg of initial body weight, kept into metabolic cages were used. Experiment one compared the metabolic balances of animals fed with dry corn and high moisture diets. The experiment two evaluated the digestibility of high moisture corn silage. In both experiments, the design was completely randomized. Each experiment had two treatments, four repetitions of one animal. The grains corn dry diet (T1) was the control treatement for two experiments. The substitution of the dry corn for high moisture corn did not influence (P>0,05) the balances of the nitrogen, phosphorus, oil and energy. The digestibility of the dry matter, crude energy and metabolizável energy of the high moisture corn were higher than the dry corn ones.